Optimizing Holistic Education for Sustainable Development - Hussein, Dr. Adan Maalim (International Journal of Scientific Research and Management (IJSRM), 2025)
Institutions of higher learning are society's primary tools for advancing knowledge. In educational institutions, knowledge management plays a crucial function. Administrative research such as student service, human resources systems, and teaching and learning processes can be independently identified and studied by educational institutions. More flexibility in the decision-making, teacher advancement, and learning processes can result from the usage of knowledge management systems. Nonetheless, there are several obstacles in the way of the successful and efficient implementation of knowledge management in the classroom. Examining knowledge, the value of knowledge management (KM), factors that support it, its application in education, and the difficulties and constraints of KM in educational institutions are the objectives of this study. Knowledge management is presently at the center of research and education in terms of advancement and growth on a global scale. Furthermore, this study examines methods for maintaining knowledge management in educational institutions, which can help address issues in education, and evaluates the idea of knowledge management from an educational standpoint. Primary data, which was gathered through content analysis of academic and professional knowledge management in education and training in institutions, is necessary for the approaches used to construct knowledge management. The study's conclusions show that during the previous four to five years, more people have had access to knowledge management in training and education programs in educational institutions.keywords: knowledge, importance of knowledge management(km), factors supporting knowledge management, application of knowledge management in education, challenges and limitations of knowledge management (km) in an educational institution